Global Indian diaspora : history, culture, and identity - Sahoo, Ajaya Kumar; Kadekar, Laxmi Narayan (Jaipur : Rawat Publications, 2012)
Contributed articles.
Includes bibliographical references and index.
Keywords: East Indian diaspora; East Indians -- Foreign countries